Genetic databases in the era of ‘DSI’ benefit-sharing - Rouard, Mathieu; Scholz, Amber Hartman; Halewood, Michael (Elsevier, 2025)
Genetic databases drive research by enabling open access. Recently, parties to the Convention on Biological Diversity agreed on new rules for sharing benefits from the use of digital sequence information (DSI) which upholds open access, and also imposed new requirements for data depositors, database managers, and users.